Unmet contraceptive needs among female sex workers (FSWs) in semi urban Blantyre, Malawi - Donatien Twizelimana; Adamson S. Muula (BMC, 2021)
Abstract Background Research has paid limited attention to understanding factors that are associated with unmet contraceptive needs among female sex workers. In order to fill this knowledge gap, we estimated the prevalence of unmet contraceptive needs and examined associated factors among FSWs in semi urban Blantyre, Malawi. Methods We used systematic sampling to recruit 290 female sex workers in semi urban Blantyre between February and March 2019. In this cross sectional study, we used questionnaire interviews to collect quantitative data. We calculated the mean and standard deviation for continuous variables and proportions for categorical variables to describe the data. Logistic regression analysis was used to investigate the association between unmet needs (the outcome variable) and explanatory variables such as: having a steady partner, fear of contraceptives' side effects and having a history of sexually transmitted infections. Results Out of the 290 study participants 102 (35.2%) reported unmet contraceptive needs. The following factors were significantly associated with unmet contraceptive needs in multivariate analysis: female sex workers' history of physical and sexual violence by clients [OR 3.38, 95% CI (1.10, 10.43)], p < 0.03, participants with a steady partner [OR 3.28, 95% CI (1.89, 5.68)], p < 0.001, and participants who feared side effects of contraceptives [OR 2.99, 95% CI (1.73, 5.20)], p < 0.001. Conclusion Reproductive Health services should address barriers to contraceptives use for instance: violence by female sex workers' clients, fear and misinformation on contraceptives. There is need to improve awareness of contraceptives. Specific health promotion interventions on female sex workers engaged in a steady partnership are recommended. It is important to enhance the knowledge, attitudes, and counseling skills of health care providers in order to address unmet contraceptive needs among female sex workers in semi-urban Blantyre. Plain English summary Unmet contraceptive needs are defined as lack of contraceptives use in heterosexually active women of childbearing age who do not wish to become pregnant. Unmet contraceptive needs are the main cause of short inter-pregnancy intervals, early childbearing, physical abuse, unintended pregnancy, poor maternal and child health outcomes. Several studies have documented low contraceptives use among female sex workers (FSWs), but research has paid limited attention to understanding factors associated with unmet contraceptive needs among this population in semi urban Blantyre Malawi. In order to fill this knowledge gap, we estimated the prevalence of unmet contraceptive needs and examined factors that were associated with unmet contraceptive needs among FSWs in semi urban Blantyre, Malawi. We recruited 290 FSWs and collected quantitative data. These data were analyzed to obtain descriptive statistics. Logistic regression analysis was used to investigate the association between unmet contraceptive needs (the outcome variable) and explanatory variables such as: FSWs with history of physical and sexual violence by clients, having a steady partner, fear of contraceptives' side effects and having a history of sexually transmitted infections. Out of the 290 FSWs, 35% reported unmet contraceptive needs. The following factors were significantly associated with unmet contraceptive needs in multivariate analysis: FSWs' history of physical and sexual violence by clients, participants with a steady partner and participants who feared contraceptive side effects. Sexual and Reproductive Health services should address barriers to contraceptives use, female sex workers exposure to violence, having a steady partners and concerns about side effects. There is also a need to improve the knowledge, attitudes, and counseling skills of health providers in order to address unmet contraceptive needs among FSWs.